Have there been efforts to integrate malaria and schistosomiasis prevention and control programs? A scoping review of the literature. - Claudia Duguay; Sydney Raduy; Engluy Khov; Natacha Protopopoff; Cindy Feng; Alison Krentel; Manisha A Kulkarni (PLoS Neglected Tropical Diseases)
Malaria and schistosomiasis are two important parasitic diseases that are a particular threat to young children and pregnant women in sub-Saharan Africa. Malaria and schistosomiasis prevention and control strategies primarily focus on the distribution of long-lasting insecticidal nets and the delivery of praziquantel tablets to at-risk populations in high burden settings through mass drug administration, respectively. The objective of this scoping review was to identify previous efforts to integrate malaria and schistosomiasis prevention and control programs in the literature and to summarize the strategies and approaches used in these programs following the PRISMA-ScR guidelines. We reviewed published and grey literature using a combination of keywords and search terms following themes surrounding "malaria", "Plasmodium falciparum", "Anopheles", "schistosomiasis", "Schistosoma haematobium", "Schistosoma mansoni", and "snails". Neither a date limit nor relevant terms for prevention and control were used. Out of 6374, eight articles were included in the scoping review-three articles investigated the integration of mass drug administration for schistosomiasis with the administration of antimalarials, four articles investigated the effect of administering antimalarials on malaria, schistosomiasis, and their co-infection, and one article assessed the impact of an educational intervention on malaria and schistosomiasis knowledge and preventative behaviors. Our findings suggest that there is an opportunity to link disease control programs to increase access and coverage of interventions to improve outcomes for malaria, schistosomiasis, and their co-infection. Further research is needed on the potential benefits, feasibility, and cost-effectiveness of integrating malaria and schistosomiasis prevention and control programs.